Modelling the Impact of Caregiving Burden on Psychological Distress with the Mediating Role of Social Support among Mothers of Children with Autism Spectrum Disorder - Shishehfar , Sepideh; Kashani Vahid , Leila; Vakili, Samira; Azizi , Mohammadparsa (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The study aims to investigate the relationship between caregiving burden, social support, and psychological distress among mothers of children with autism spectrum disorder (ASD). It specifically examines the mediating role of social support in the linkage between caregiving burden and psychological distress.Methods and Materials: This cross-sectional study utilized Structural Equation Modeling (SEM) to analyze data from a sample of mothers of children with ASD. Key variables included caregiving burden, perceived social support, and psychological distress measured with standardized tools. The statistical analysis was conducted using SPSS-26 for preliminary data handling and descriptive statistics, while AMOS-22 was utilized for the SEM analysis to explore the relationships between caregiving burden, perceived social support, and psychological distress among the participants.Findings: Results indicated that caregiving burden significantly predicts psychological distress (β = 0.19, p < 0.001), and social support plays a crucial mediating role in this relationship. Higher levels of perceived social support were found to significantly mitigate the impact of caregiving burden on psychological distress (β = -0.37 for social support to distress, and β = -0.43 for burden to support, p < 0.001 for both). The model fit indices (CFI = 0.95, TLI = 0.94, RMSEA = 0.06) confirmed a good fit for the SEM model.Conclusion: The study shows the significant impact of caregiving burden on psychological distress among mothers of children with ASD. More importantly, it indicates the critical role of social support as a buffer in this relationship. These findings advocate for enhanced social support systems and interventions to alleviate the psychological distress experienced by these mothers, thereby improving their overall well-being.